Optimizing Numeracy To Support Climate Change Education In Elementary Schools: A Systematic Literature Review - Maharani, Fitriya; Suwandayani, Beti Istanti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
Climate change is a global challenge that requires education at the elementary school level to foster environmental awareness. Numeracy plays a vital role in enabling students to read, interpret, and use environmental data, which is essential for understanding climate change. However, the integration of numeracy with climate change education in primary schools has received inadequate attention. This study aims to systematically review literature on the integration of numeracy in climate change education in elementary schools. It investigates the various approaches, challenges, and outcomes of numeracy in environmental education, focusing on the development of students' ecological awareness and data interpretation skills. A systematic literature review using the PRISMA approach was employed. Articles were sourced from Scopus, with 46 initial articles screened, and 11 relevant studies from 2015-2024 were selected. Data analysis was conducted using VOSviewer for keyword co-occurrence visualization. The review revealed emerging trends in utilizing contextual numeracy through data visualization, project-based learning, and interdisciplinary modules. These strategies were effective in enhancing students' ecological literacy and climate change awareness. The study concludes that integrating numeracy with real-world climate data in primary education enhances students' understanding of climate change. Challenges remain in teacher resources and motivated numeracy, but the development of context-based curriculum models can address these gaps and improve environmental education.